Private Finance as Public Planner: A Channel-Based Framework for Equitable and Strategic Climate Transitions - Sohaib Uz Zaman; Muhammad Mohtashim; Syed Hasnain Alam (Research Journal of Psychology, 2024)
The investigation examines private financial institutions which act as decentralized development planners in Pakistan to explain how institutional channels enable financial actors to guide corporate ESG behavior. The worldwide increase in sustainable finance activity has resulted in limited academic research on its actual effects in emerging economies. The research analyses the effectiveness of influence channels such as reputation, divestment, litigation and ratings which shape sustainable productive investment. This research employed a cross-sectional design to gather data using structured questionnaires from Pakistani professionals working in banking, insurance, and regulations sectors who focus on ESG matters. SmartPLS 4.0 performed Partial Least Squares Structural Equation Modeling on the data which verified the direct and mediated relationships that exist between ten elements of the Channels of Influence framework. Multiple moderating factors such as coalition-building and litigation strengthen the force that ESG capital has over sustainable investments. The research presents a specific multivariate model that sheds light on ESG finance operations within developing economic frameworks. The research provides strategic guidance to Pakistani regulators and investors about aligning institutions and policies to strengthen climate finance transitions.